Diagnosis of Equine Metabolic Syndrome in the Colombian Creole Horse in the Bogota Savannah - Rosas Gutiérrez, Magnolia (2023)
Equine metabolic syndrome (EMS) is a disorder of endocrine and metabolic origin associated mainly to insulin, obesity and laminitis dysregulation. It is argued that the Colombian Creole horse (CCC) is predisposed to develop it; however, there are no specific studies for this breed. The objective of the study was to diagnose the EMS based on the relationship between obesity, regional adiposity, hyperinsulinemia, hypertriglyceridemia and hyperleptinemia and associate it with the development of clinical signs of laminitis in CCC horses in the savannah of Bogotá. Two groups were evaluated: 10 clinically healthy horses as a control group and 30 obese (body condition >7/9) with regional adiposity in the neck as clinical signs associated with the EMS. The levels of glucose, insulin, leptin and triglycerides were determined, as well as the combined insulin-glucose test (TIGC) in the two groups. There were no significant differences between groups in glucose levels during the TIGC, but in insulin, both at minute 0 (p=0.0193) and at minute 45 (p=0.018). There were no significant differences in triglycerides between groups. The values resulting from leptin were not conclusive due to problems with measurement technique. There were horses of the obese group with signs associated with laminitis, but without significant differences in measurements that could be related to the presentation of clinical signs. There was clear evidence of insulin dysregulation in obese horses, as well as some cases individually evaluated where the results were compatible with those reported in the EMS.